Integrasi Paradigma Ekonomi Islam Berbasis Lingkungan dalam Pendidikan Islam: Relevansi Pemikiran M. Umer Chapra - Abidin Ahmad; Daud Duli; Hasanah Purnamasari; Putri Aldillah Bapang; muh Amiruddin Salem (ISEDU : Islamic Education Journal, 2025)
This conceptual study examines the relevance of M. Umer Chapra's environmentally grounded Islamic economic thought to the aims and practices of Islamic education. It departs from the global environmental crisis, which is not merely ecological but also moral, social, and spiritual, and from the limited capacity of value-free education to cultivate ecological responsibility among learners. Employing a qualitative library research design with a descriptive-critical content analysis of Chapra's works and supporting literature on maqasid al-shariah, fiqh al-bi'ah, and Islamic education, the study reconstructs Chapra's principles of justice, maslahah, khilafah, and holistic well-being (falah) into an educational framework. The findings indicate that Chapra's paradigm can enrich the objectives of Islamic education by positioning the learner as a khalifah responsible for preserving the environment (hifz al-bi'ah), and can be integrated into curriculum content, learning materials, character education, and the pedagogical culture of madrasah and pesantren. The study concludes that reconstructing Chapra's environmentally oriented Islamic economics as an educational value system offers a meaningful basis for nurturing ecologically conscious, just, and responsible Muslim learners in line with the objectives of twenty-first-century Islamic education.